2022
DOI: 10.3389/fpsyg.2022.967931
|View full text |Cite
|
Sign up to set email alerts
|

An empirical investigation between brand orientation and brand performance: Mediating and moderating role of value co-creation and innovative capabilities

Abstract: This study analyses the function of value co-creation in mediating the relationship between brand orientation, brand performance, and innovation capacities in China’s small and medium-sized enterprises (SMEs). Using the organization’s size differential characteristic, additional testing of these criteria across disaggregated SME levels is performed. The empirical examination of 240 enterprises in an emerging market setting was conducted using Structure Equation Modeling (SEM). According to the results of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 50 publications
0
0
0
Order By: Relevance
“…Studies on the adoption and application of various strategic orientations in organizations have attracted increasing attention from researchers, academics, and industry professionals, particularly due to the importance of management decisions that allow firms to achieve higher performance levels (Yueqiang, 2022). Therefore, SMEs that give greater value to their brands and have a better orientation of their brands, generally have greater success in financial markets, compared to those competitors that have a lower brand orientation (Yueqiang, 2022). Thus, in a highly competitive and globalized market, companies, particularly SMEs, seek to obtain more competitive advantages, as well as greater business performance, for which brand orientation plays an essential role (Wong & Merrilees, 2005).…”
Section: Preliminary Notesmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies on the adoption and application of various strategic orientations in organizations have attracted increasing attention from researchers, academics, and industry professionals, particularly due to the importance of management decisions that allow firms to achieve higher performance levels (Yueqiang, 2022). Therefore, SMEs that give greater value to their brands and have a better orientation of their brands, generally have greater success in financial markets, compared to those competitors that have a lower brand orientation (Yueqiang, 2022). Thus, in a highly competitive and globalized market, companies, particularly SMEs, seek to obtain more competitive advantages, as well as greater business performance, for which brand orientation plays an essential role (Wong & Merrilees, 2005).…”
Section: Preliminary Notesmentioning
confidence: 99%
“…The brand concept is one of the marketing activities, which has been analyzed and discussed relatively little in marketing literature (Wong & Merrilees, 2005). Likewise, various researchers, academics and marketing professionals have tried to rationalize and make efficient brand management systems which include, for example, brand perception, brand loyalty, brand knowledge, brand differentiation, brand equity, brand rewards, brand proliferation, brand image, and brand orientation (de Chernatony, 1992; Aaker, 1996;Keller, 2003), thereby seeking to firms, mainly small and medium-sized (SMEs), achieve not only greater business performance but also their own survival (Yueqiang, 2022). Furthermore, Piha et al (2021) considered that the relationship between brand orientation and business performance is generally affected by external influences, while other researchers concluded that given the competitiveness level existing in business environment and implementing only a brand orientation.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations